Complications and accidents in third molar exodontics: A literature review (Research, Society and Development, 2025)
Third molars are the last teeth to develop, and their eruption occurs between 17 and 25 years of age. Due to their late emergence, a lack of space in the dental arch is common, which can result in partial or complete eruption, leading to dental impactions. This group of teeth is particularly prone to impaction, and extraction is often indicated. The objective is to list the main complications and accidents associated with third molar extraction, in addition to identifying the risk factors that may favor their occurrence. This is a narrative review of the literature. Information was collected through comprehensive searches in the Periódico Capes, Biblioteca Virtual em Saúde (BVS), and Google Scholar databases, from 2015 to 2025. The complications and accidents most frequently reported in the literature include: dry socket, nerve injuries, edema, trismus, pain, infection, mandibular fracture, hemorrhage, and oroantral communication. These complications are often related to flaws in surgical planning and the patient's systemic conditions. The main way to prevent these complications and accidents involves performing an appropriate clinical and radiological examination, developing a detailed surgical plan, carefully instructing the patient on postoperative oral hygiene, and ensuring proper medication use. Given the complexity of third molar extraction and the varying factors that influence the occurrence of these complications and accidents, we suggest the need for further studies in this field to deepen our understanding of this topic.